Lugares y no lugares en el espacio urbano, caso de estudio primera línea de metro de Bogotá en las localidades Kennedy y Puente Aranda (2022)
The current degree work consists of the analysis of problems that affect the intervention of mass mobility systems in the urban environment of the city of Bogotá regarding the importance of the pedestrian along with the creation of public space and active mobility, which are influenced by the support of public transport and the different urban environments that are created from the intervention of the first metro line in the city, therefore the quantitative and qualitative variables applied in different case studies where it is presented are analyzed. this means of elevated mass transportation, in order to generate the adequate insertion of the project and the generation of quality public spaces and the conception of places for the population. From this, the design of urban spaces that are possibly disconnected or that generate a negative social environment is proposed, this through a research methodology where initially there is a descriptive investigation where the urban environments of different referents that prese